(untitled) (AYUSHDHARA, 2023)
Kushtha is described in several sources of Ayurvedic literature. Many skin illnesses are classified as Kustha, and can cause substantial functional and social difficulties. Kushtha are classified into seven Maha Kushtha types and eleven Kshudra Kushtha types. Mandal kustha is classified as a form of Maha kustha. Shweta rakta vikshat, Sthir, Styaan, Snigdha, Utsanna Mandalam, Anyonya sanyuktam, and Krichham are symptoms of Mandal kushtha. In this study, Mandal kustha was compiled from Bruhattrayee (Charak samhita, Sushrut samhita, Vagbhatta) and Laghutrayee (Madhav Nidan, Sharangdhar Samhita, and Bhavprakash) etc.